PENGARUH PENGGUNAAN MEDIA BALOK TERHADAP KREATIVITAS ANAK USIA 5-6 TAHUN (Penelitian Eksperimen di TK Al – Khairiyah Cilegon - Banten) - Pranindya Anisa; Ratih Kusumawardani; Kristiana Maryani (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2018)
Creativity is the ability that everyone has to create or produce something new through his imagination. The imagination generated by one’s thinking can lead to creativity. Beams are one of the educational game tools generally made of wood. The usage on creativity of children aged 5-6 years. Research method using quasi experimental method with a sample of 40 children in the experimental class and 40 children in the control class. Data was analyzed using SPSS 22. purpose of the study was to determine the effect of mediThe results showed that the percentage of independent statistical sample test value of significance post-test of creativity for experimental class and control class that is 0,109 0,05 mean data of creativity post-test for experiment class and control class that is H1 = there is a significant influence on the creativity of children 5-6 years. The mean value of experimental class is mean = 32,8958, standard deviation = 4,88262, standard error mean = 0,70475, mean value mean control class mean mean = 20,2917 standard deviation = 3,77539, standard error mean = 0,54493 obtained ttable = (0,05/2 ; 96 -2 – 1) = (0,025 ; 93) = 1,989 ttable with dk = 24 + 24 + 2 = 50 and a =0,05 1,109, thitung = 14,148H1 : received. Therefore, the child’s creativity ability can be said to increase when given treatment in the ezperimental class and the child raises the developmental indicator independently. It can be concluded, that through learning with the media beam can improve the creativity of children aged 5-6 years in kindergarten al-khairiyah cilegon-banten.